MODEL OF OBLIGATION REGULATORY CONSTRUCTION AS LEGAL PROTECTION EFFORT TO CAPITAL MARKET INVESTORS BASED DIGNITY JUSTICE - Tommy Leonard; Heriyanti Heriyanti (Jurnal Pembaharuan Hukum, 2018)
The research objective is to create a model for regulation of construction obligations as a form of legal protection against Indonesian capital market investors based on dignity justice which is a new strategy for strengthening the role of government in the regulation of the obligation yield. The resulting model in this study in particular has a purpose as an offer or alternative solutions both a legislative function in the realm of the executive and Parliament to produce a obligation regulation. The method that will be used through the stages include: mapping existing condition of construction which has been used, the mapping of potential executives (leading sector) and the Council, evaluating regulations that have been produced so far, identify and evaluate the constraints faced in stage construction policy , identify opportunities and strategies and formulate a model of construction that can be developed, p enekanan in order construction regulations do executive and Parliament in order to generate regulatory-based justice and legal certainty